1993
DOI: 10.1063/1.355147
|View full text |Cite
|
Sign up to set email alerts
|

Cathodoluminescence and microRaman analysis of oxygen loss in electron irradiated YBa2Cu3O7−x

Abstract: The effect of oxygen loss on the luminescence of YBazCu307-, has been investigated by cathodoluminescence (CL) in the scanning electron microscope (SEM) and by Raman microprobe measurements. The results herein indicate that a CL band at 530 nm is related to oxygen loss rather than to impurity phases such as YZ03 formed in the material by electron irradiation in the SEM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…The increase of the 2.3 eV band indicates that some of the deformation-induced defects are the oxygen vacancy related defects detected at the growth features as well as in YBa 2 Cu 3 O 7Ϫx ceramics after annealing or electron irradiation treatments. [10][11][12] Oxygen vacancy generation and the related luminescent effects, caused by indentation or other deformation treatment, have been often described in the case of some ionic crystals, mainly MgO, e.g., Ref. 18.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase of the 2.3 eV band indicates that some of the deformation-induced defects are the oxygen vacancy related defects detected at the growth features as well as in YBa 2 Cu 3 O 7Ϫx ceramics after annealing or electron irradiation treatments. [10][11][12] Oxygen vacancy generation and the related luminescent effects, caused by indentation or other deformation treatment, have been often described in the case of some ionic crystals, mainly MgO, e.g., Ref. 18.…”
Section: Resultsmentioning
confidence: 99%
“…Miller et al 7 observed that insulating phases in YBa 2 Cu 3 O 7Ϫx emit higher CL signals than nominally metallic phases, and other CL microscopy works indicated the relationship between certain luminescence features and oxygen-depleted zones in YBa 2 Cu 3 O 7Ϫx . [8][9][10][11] In particular a 2.3 eV emission band was related to centers involving oxygen vacancies. A band at the same energy has been reported in CL microscopy studies of Tl 2 Ba 2 CuO 6ϩx ͑Ref.…”
Section: Introductionmentioning
confidence: 99%
“…6 We obtained similar results in the CL characterization of Bi-2212 single crystals, 7 in which preliminary REBIC investigations also revealed PAT contrast related to growth steps. A correlation between oxygen depletion and the mentioned 2.4 eV emission has been established not only in YBCO, 3 but also in other HTSC like Tl 2 Ba 2 CuO 6ϩ␦ ͑Ref. 5͒ and Bi-2212.…”
mentioning
confidence: 99%
“…1 Structural and composition changes induced by transformation of the phase composition and by oxygen losses in electron irradiation have been detected visually with the aid of a scanning electron microscope (SEM) (Ref. 2) and by spectral methods [3][4][5][6] in YBa 2 Cu 3 O 7-x and Bi 2 Sr 2 CaCu 2 O 8+x . Oxygen depletion of the surface is probably one of the major phenomena encountered in the electronbeam irradiation of superconductors; the more detailed investigation of this process requires new experimental approaches suitable for local quantitative measurements otherwise unattainable by standard methods.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The investigation of irradiationinduced electronic processes in a superconductor broadens our concepts of its electronic structure and real defects. The intentional alteration of the nature of the properties in individual parts of the superconducting matrix can provide a basis for local modification of the surface.…”
Section: Introductionmentioning
confidence: 99%